A psychological aspect of globus pharyngeus - Rana, Vasundhara; Srivastava, Rani; Malhotara, Tarun; Kumar, Ashok (International Journal of Research in Medical Sciences, 2025)
Background: Several psychological factors are included in globus pharyngues. The study aims to analyze psycho-social correlates of globus pharyngeus. Method: This study is an observational study in individuals taken from various Delhi and NCR ENT clinics like Krishna Nagar ENT specialist Clinic (Delhi), Hargobind Enclave ENT specialist Clinic (Delhi), Santosh Medical Hospital (Delhi), Brij Vihar ENT specialist Clinic. (UP). ENT specialist has diagnosed individuals and they have undergone Endoscopies, treatment for Reflux for 3 weeks at least and still not recovered were taken for the testing. The adults 1from the age range of 18 years to 64 years according to National Institute of Health had participated in this study. After data collection Person Correlation was applied through SPSS. Result: Total 100 Adults have participated in the research, results of correlation indicated that globus and depression found to be having no correlation (r =-0.115), Globus and Anxiety has an negative correlation (r= -0.330, p<0.01), Globus and Stress has an correlation (r=0.198, p<0.05) , Globus and Psychoticism has an correlation (r=0.282, p<0.01), Globus and Neuroticism it found to be having no correlation (r=0.139), Globus and Extraversion it found to be having no correlation (r=-0.196), globus and social support has an correlation (r=0.220, p<0.05). Conclusion: Patients with Globus complain of pain without any physical illness these patients also have psychosocial problems. To concluded from the study, it shows that globus has high levels Anxiety, Stress, Psychoticism and low Social Support.